Synthesis and physical properties of multiferroic BaDyFeO4 - Le, Thi Phuong Thao; Do, Danh Bich; Dinh, Thanh Khan; Tran, Tuan Anh; Le, Vu Truong Son; Dang, Ngoc Toan; Nguyen, Truong Tho (Hue University Journal of Science: Natural Science, 2023)
Materials exhibiting magnetoelectric effects have drawn great interest because of their intriguing physical phenomena and potential applications in electronic devices. The magnetoelectric (ME) coupling makes the materials promising for use in multifunctional devices with electric-field-tunable magnetism and magnetic-field-controlled ferroelectricity. Very recently, a strong ME effect has been found in the BaRFeO4 system (R is a rare-earth element), in which the ferroelectricity is driven by the onset of a long-range cycloidal antiferromagnetic order of Fe spins. However, previous studies have shown how complicated the synthesis procedure is to obtain single-phase samples of the materials. In this work, we present a simple and easy fabrication process to synthesise high-quality BaDyFeO4 using the conventional solid-state reaction method. The structural, morphological, and optical properties of the synthesised sample were investigated by means of X-ray diffraction, scanning electron microscopy, and UV-Vis spectroscopy, respectively. The sample was formed from high-quality microparticles. The X-ray diffraction study reveals the single-phase nature of the sample adopting the Pnma orthorhombic structure without any impurity phases. The detailed structural parameters were refined with Rietveld refinement. The sample demonstrates a direct gap semiconducting behaviour. The experimental results of the structural and electronic properties of BaDyFeO4 are complemented by density functional theory (DFT) calculations.